The Impact of Alkyl‐Chain Purity on Lipid‐Based Nucleic Acid Delivery Systems – Is the Utilization of Lipid Components with Technical Grade Justified?. Issue 16 (23rd July 2019) - Pawlowska, Dorota; Janich, Christopher; Langner, Andreas; Dobner, Bodo; Wölk, Christian; Brezesinski, Gerald
Abstract: The physicochemical properties and transfection efficacies of two samples of a cationic lipid have been investigated and compared in 2D (monolayers at the air/liquid interface) and 3D (aqueous bulk dispersions) model systems using different techniques. The samples differ only in their chain composition due to the purity of the oleylamine (chain precursor). Lipid8 (using the oleylamine of technical grade for cost‐efficient synthesis) shows lateral phase separation in the Langmuir layers. However, the amount of attached DNA, determined by IRRAS, is for both samples the same. In 3D systems, lipid8 p forms cubic phases, which disappear after addition of DNA. At physiological temperatures, both lipids (alone and in mixture with cholesterol) assemble to lamellar aggregates and exhibit comparable DNA delivery efficiency. This study demonstrates that non‐lamellar structures are not compulsory for high transfection rates. The results legitimate the utilization of oleyl chains of technical grade in the synthesis of cationic transfection lipids. Abstract : The lipid formulations of cationic lipids of different purity qualities (i. e. a cheap version consisting of a technical mixture and an expensive, high‐purity version) are compared regarding structural parameters, DNA‐binding capacity, and transfection efficiency. The results justify the utilization of technical‐purity‐grade unsaturated compounds for the synthesis of cationic lipids for lipofection.